The origins of the South African Reserve Bank - Gelb, Stephen (My University, 1984)
The South African Reserve Bank was opened on June 30, 1921, having been established under the provisions of the Currency and Banking Act (No. 31 of 1920). There was at the time only one other central bank in the British Empire, the Bank of England itself. The Act had been drafted after a situation of chaos developed in the South African monetary system. In March 1919, when the British Government abandoned its wartime rate of exchange between the pound sterling and gold, the pound depreciated to produce a ‘gold premium’. British gold sovereigns, obtainable for 20s. from banks in S.A. now commanded a considerably higher price outside the country. Large numbers of coins were now smuggled out, contravening the S.A. government's ban on their export. Although the premium was effectively keeping many of the goldmines afloat, the S.A. banks found themselves in a disastrous situation, being forced to import, and provide to the public at 20s. increasing numbers of coins purchased at the premium price. The eventual government response was to withdraw sovereigns from circulation, and to establish the Reserve Bank to prevent a recurrence of such an untenable situation. There was thus a fundamental restructuring of the form of regulation of the S.A. monetary system.
African Studies Seminar series. Paper presented September, 1984
Keywords: Banks and banking. South Africa; South African Reserve Bank